2022
DOI: 10.1097/mat.0000000000001708
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modeling of the Penn State Fontan Circulation Assist Device

Abstract: To address the increasing number of failing Fontan patients, Penn State University and the Penn State Hershey Medical Center are developing a centrifugal blood pump for long-term mechanical support. Computational fluid dynamics (CFD) modeling of the Penn State Fontan Circulatory Assist Device (FCAD) was performed to understand hemodynamics within the pump and its potential for hemolysis and thrombosis. CFD velocity and pressure results were first validated against experimental data and found to be within the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…A total of 10 trials [5][6][7][8][9][10][11][12][13][14] were identified which fulfilled the inclusion criteria as well as the needed outcome parameters; while another 10 trials were excluded due to unmet outcomes [15][16][17][18][19][20][21][22]. Some of the included trials involved different settings in terms of pump speed or terms of device design, a total of 23 sets of adjustments were finally analyzed in terms of their impact on IVC and SVC pressure and resultant flow rate.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 10 trials [5][6][7][8][9][10][11][12][13][14] were identified which fulfilled the inclusion criteria as well as the needed outcome parameters; while another 10 trials were excluded due to unmet outcomes [15][16][17][18][19][20][21][22]. Some of the included trials involved different settings in terms of pump speed or terms of device design, a total of 23 sets of adjustments were finally analyzed in terms of their impact on IVC and SVC pressure and resultant flow rate.…”
Section: Resultsmentioning
confidence: 99%
“…The connecting chamber and the compression device require a surgical approach for their insertion, while intravascular pump designs are inserted via a transcatheter route. This has been reflected in the number of in-vivo trials across the three designs, which clearly shows that most of the trials (67%) employed in the intravascular design were in-vivo compared to 0% of compression devices' trials and 9% of the connecting chamber designs [5][6][7][8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Investigative collaboration with bioengineers and mathematicians has opened a new horizon in the research for mechanical circulatory support even in Fontan circulation, resulting in a large number of publications on the topic (177,238,(246)(247)(248)(249)(250)(251).…”
Section: Mathematical and Computational Fluid Dynamic Studiesmentioning
confidence: 99%